2019
DOI: 10.3389/fpsyg.2019.00590
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Predictors of Unhealthy Eating Attitudes in Young Adults

Abstract: The objective of this study was to determine the predictive role of psychological risk factors for restrained and compulsive eating in young women and men. We examined the relationship between resilience, impulsivity, emotional intelligence and self-esteem, and restrained and compulsive eating. It was assumed that resilience and impulsivity can directly explain unhealthy eating attitudes (restrained and compulsive: both emotional eating and external eating). The study group comprised 211 individuals (105 men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 88 publications
1
21
0
4
Order By: Relevance
“…Recent research has shown that commercials and standards of physical appearance and body image promoted by the mass media usually affect how appealing body image should look like (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The influence produced by media, advertising, websites, and personal networks is examined (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that commercials and standards of physical appearance and body image promoted by the mass media usually affect how appealing body image should look like (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The influence produced by media, advertising, websites, and personal networks is examined (18).…”
Section: Introductionmentioning
confidence: 99%
“…However, not many studies determine the strength of the interrelationship between body image standards presented by the mass media and restrictive and bulimic behavior in a homogeneous population of women and men in term of age, Body Mass Index (BMI), and socioeconomic status. Most of this research was conducted on groups of girls and women (5,9,(19)(20)(21)(22)(23). Only a few articles emphasize the importance of the relation between the internalization of socio-cultural standards of attractive appearance and ideal athletic body image and self-assessment in men and it is possible these variables predict restrictive and bulimic (compulsive) eating behavior in men too (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…The product with NWLs can generate some degree of dissatisfaction or disappointment in the consumer for not making a good decision about food. This disagreement can psychologically affect consumer self-esteem, both in men and women [ 43 ]. Therefore, it is imperative that food-producing companies must reformulate their products so that consumers have access to less harmful food for their physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…These differences seem to disappear over the age of 30. Self-esteem for women in the period of adolescence and young adulthood seems to be more associated with how physical attractiveness is promoted in media coverage [1,2,37]. On the other hand, Robins et al referred to the known developmental theory which indicated that full adulthood is associated with acquisition of psychological maturity and redirecting attention to self-improvement and being productive.…”
Section: Discussionmentioning
confidence: 99%
“…Although this issue seems to be important for developing scientific knowledge, which could support preventive healthcare and promote pro-health behaviours towards the body. Available sources of literature indicate that modern scientists often search for psychological and sociocultural factors influencing the development of the body image in the groups of healthy people and in groups of people presenting various types of eating disorders [1,2,3]. Moreover, scientific measurements of the relation between social competences and self-esteem, which include self-assessment of the body, have appeared for many years among the research topics conducted on adult population [4,5].…”
Section: Introductionmentioning
confidence: 99%